Manajemen Mutu Terpadu dalam Pendidikan Islam - Ayu Annisa; Pinkan Gyfend (Jurnal Syntax Transformation, 2021)
The principle of management is the overall supervision of all members of the educational institution of the activities of the Organization. The application of Total Quality Management (TQM) means that all school members are responsible for the quality of education, so that all parties involved in the academic process in Islamic educational institutions, ranging from school/madrasah committees, principals/madrasahs, heads of administration, teachers, students with employees must fully understand the nature and purpose of this education. In other words, every individual involved must understand what the purpose of education is. Without a thorough understanding of the individuals involved, it is impossible to implement TQM. This management system greatly minimizes bureaucratic processes. The bureaucratic system of Islamic educational institutions will hinder the potential development of the institution itself. Therefore, this study aims to explain the meaning of Integrated Quality Management, Explain the Elements of Integrated Quality Management in Islamic Education and Explain the Principles, Models and Benefits of Integrated Quality Management. This research method uses a qualitative approach, where the method contained in this study is a library research method. The application of TQM in the field of education is carried out by people who are experts in their fields with more efforts from the education leadership so that the quality of education is truly guaranteed. In achieving these results, the implementation of TQM in Islamic education organizations needs to be carried out actually not half-heartedly. The implementation of TQM in educational organizations, especially in Islamic educational institutions, is indeed not easy.